2011
DOI: 10.1016/j.anpedi.2010.08.003
|View full text |Cite
|
Sign up to set email alerts
|

¿Es la persistencia de ductus arterioso un factor de riesgo para la retinopatía del prematuro?

Abstract: The presence of PDA does not increase the risk of developing ROP or its severity, once considered the effect of gestational age in PDA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…sepsis, intraventricular hemorrhage, patent ductus arteriosus and hydrocephalus, respiratory distress syndrome, hyperbilirubinemia, use of surfactant). Many studies have suggested their association with ROP development [19, 32], while others did not [33, 34]. Among them, respiratory distress syndrome was the only variable that showed statistically significant association with the development of ROP but only in univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…sepsis, intraventricular hemorrhage, patent ductus arteriosus and hydrocephalus, respiratory distress syndrome, hyperbilirubinemia, use of surfactant). Many studies have suggested their association with ROP development [19, 32], while others did not [33, 34]. Among them, respiratory distress syndrome was the only variable that showed statistically significant association with the development of ROP but only in univariate analysis.…”
Section: Discussionmentioning
confidence: 99%